Palgrave Study Skills: The International Student Handbook - Johnson, Karen; Wells, Lisa (Journal of International Students, 2014)
The International Student Handbook addresses the needs of students whose first language is not English. Whether they are future or current students, as non-native English speakers who study at English-speaking universities, they will deal with issues ranging from adapting to the new academic culture to understanding the nuances of the language. This practical handbook can help prepare students adjust to the academic rigors of Western universities, understand the university culture, improve their English, and become successful university students. The three authors report a combined history of teaching at universities in 12 different countries.